Sustainable Wastewater Treatment Technologies for Thailand - Wongburi, Praewa (My University, 2018)
Wastewater consists of valuable resources that could be recovered or reused. Still it is under threat because of ineffective wastewater management and systems. In Thailand, wastewater produced can be treated less than 25%, which means more than 75% of wastewater is inadequately treated and sent back directly into body rivers or the environment. Furthermore, the technologies that have been applied may be inefficient and unsustainable. Sense, efficiency, sustainable and simplicity are important concepts when designing an appropriate wastewater treatment system in developing countries. Wastewater treatment system should be appropriateness, effectiveness, sustainability, and straightforwardness. The objectives of this study are to review and evaluate wastewater treatment technologies and propose a method to improve or select an appropriate technology. An expert system in Excel® program is developed to find out the best solution. Sensitivity analysis is applied to compare and assess uncertain factors. Due to the different conditions of each area, the key factor of interest is varied. Furthermore, Robust Decision Making tool is applied to find out the best way to improve existing wastewater treatment facility and to choose the most appropriate wastewater treatment technology. The major conclusions supported by the results of this study are: 1. Thailand should improve wastewater treatment systems by implementing an expert system to help selecting a new technology 2. A technology should be local fitness, efficiency, sustainability, and uncomplicatedness.